Experimental investigation on the thermal performance of water cooled multi-split heat pipe system (MSHPS) for space cooling in modular data centers. (25th August 2016) - Ling, Li; Zhang, Quan; Yu, Yuebin; Liao, Shuguang
Highlights: Thermal characteristics of MSHPS are experimentally analyzed. The optimal refrigerant filling ratio was 33–42%. The system, evaporator section and CDU section thermal resistance were studied. Effects of inlet temperature of air on the thermal performance are investigated. Effects of inlet temperature of cooling water on the thermal performance are investigated. Abstract: A water cooled multi-split heat pipe system (MSHPS) was proposed to cool the space in modular data centers. It combines high thermal performance heat pipe technology with cold aisle containment architecture technology to remove heat effectively and minimize the short-circuiting of the hot air within the IT server. Experimental investigations were conducted to identify the optimal refrigerant filling ratio and the effect of different inlet air temperatures and different inlet cooling water temperatures on the unit of MSHPS. As a result of experiments, the optimal refrigerant filling ratio was found in the range from 33% to 42% with cooling capacity range from 6100 W to 6200 W and the system thermal resistance of evaporation process ranged from 0.0028 K/W to 0.0030 K/W. The effect of inlet temperature of air and cooling water were analyzed in terms of the cooling capacity, refrigerant temperature and pressure distribution along the unit of MSHPS. These results are useful for the design and operational control of the MSHPS for modular data centers.